Australian Metropolis A planning history - Hamnett, Stephen (Allen & Unwin, 2014)
The Australian Metropolis splendidly fills a huge gap in the literature on Australian cities. It is the definitive account of the history of Australian cities and the crucial role which planning has played in their genesis and growth. Spanning two centuries from the very beginning until the present day, it will instantly become a standard work'.Professor Sir Peter Hall, author of Cities in Civilisation 'From the city as public health threat to be 'improved', to the city-beautiful of architect-planners, to city plans as sites of political contest, to the recent revival of metropolitan planning, urban management and sustainability, this fascinating and thorough chronology of Australian urban planning has it all. The plans, the events, the government agencies, the different cities in their precise contexts, the decision-makers, the power relations and the paradigm shifts, all are here in clear prose, flawlessly compiled and fully-referenced by some of Australia's eminent planning historians. The Australian Metropolis will be a standard, a sought-after work of reference that also sets a fine example as an edited volume of great coherence.'Professor Ruth Fincher, Faculty of Architecture, Building and Planning, University of Melbourne The Australian Metropolis provides a single-volume introduction to the development of urban planning. It fills the need for a convenient, initial resource for anyone interested in the broad evolutionary sweep of modern planning. By setting the evolution of Australian planning within its broader societal context, The Australian Metropolis presents a balanced appraisal of positive, negative and ambivalent legacies resulting from attempts to plan Australia's major cities
Description based on publisher supplied metadata and other sources
Keywords: Geschichte 1800-2000; Stadtplanung; City planning -- Australia; City planning; Städtebau; Geschichte; Australien; Aufsatzsammlung